Youtility : why smart marketing is about help not hype - Baer, Jay, 1969- (Portfolio/Penguin, 2013)
"The difference between helping and selling is just two letters If you're wondering how to make your products seem more exciting online, you're asking the wrong question. You're not competing for attention only against other similar products. You're competing against your customers' friends and family and viral videos and cute puppies. To win attention these days you must ask a different question: "How can we help?" Jay Baer's Youtility offers a new approach that cuts through the clut;ter: marketing that is truly, inherently useful. If you sell something, you make a customer today, but if you genuinely help someone, you create a customer for life. Drawing from real examples of companies who are practicing Youtility as well as his experience helping more than seven hundred brands improve their marketing strategy, Baer provides a groundbreaking plan for using information and helpfulness to transform the relationship between companies and customers"--